The effects of cavity diameter and material type of spatial confinement on intensity of laser-induced breakdown spectroscopy. (1st January 2023) - Wang, Yiqin; Jia, Yueying; Gao, Lu; Su, Qi; Liu, Wei; Zhou, Tianchun; Xiao, Qingmei
Abstract: In this paper, we have investigated the spatial confinement effects on the spectrum intensity of tungsten plasma generated by laser-induced breakdown spectroscopy in the near-vacuum environment. The enhancement effects that vary with the diameters of the spatial confinement cylinders and with the material type are analyzed. We find that for an Al cylinder, the enhancement factor o reaches its highest value at diameter 4 mm. The primary causes behind this finding are attributed to the influences of diameter on the bounce time of shock wave propagating in the plasma as well as on the available range of spectrum collection. Moreover, the enhancement effect of Al cylinder is better than the other four types of materials: ZrO2, Al2 O3, Fe and Cu. For each of the latter four types of materials, the thermal conductivity plays a major role on the enhancement effect, whereas for Al the enhancement effect is mainly due to its extremely large reflectivity. Particularly, for cavity with a diameter of 4 mm made of Aluminum, the maximum of the enhancement factor can approximately reach as high as 15. These experimental results indicate that the signal intensity of laser-induced breakdown spectroscopy can be dramatically improved by appropriately selecting diameter and material type of the cylindrical cavity.